Neuroprostheses control interfaces based on body motion in persons with spinal cord injury - Fonseca, Lucas Oliveira da (2019)
Tese (doutorado)—Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Elétrica, 2019.